2020
DOI: 10.20944/preprints202004.0134.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Avoiding COVID-19 Complications with Diabetic Patients Could Be Achieved by Multi-Dose Bacillus Calmette–Guérin Vaccine: A Case Study of Beta Cells Regeneration by Serendipity

Abstract: Diabetes mellitus (DM) is one of the major risk factors for COVID-19 complications as it is one of the chronic immune-compromising conditions especially if patients have uncontrolled diabetes, poor HbA1c &/or irregular blood glucose levels. Diabetic patient’s mortality rates with COVID-19 are higher than cardiovascular or cancer patients. Recently Bacillus Calmette–Guérin (BCG) has shown successful results in reversing diabetes in both rats and clinical trials based on di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…Any country that produces more environmental pollutants is more likely to have coronaviruses. Findings from other researchers' studies confirm the results of this study [14][15][16][17][18]. This study showed that the emission of two gases, SF6, and CO2, had the greatest impact on the infection and death caused by the coronavirus, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Any country that produces more environmental pollutants is more likely to have coronaviruses. Findings from other researchers' studies confirm the results of this study [14][15][16][17][18]. This study showed that the emission of two gases, SF6, and CO2, had the greatest impact on the infection and death caused by the coronavirus, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Any country that produces more environmental pollutants is more likely to have coronaviruses. Findings from other researchers' studies confirm the results of this study [14][15][16][17][18]. Nitrous oxide (N2O): Although N2O gas has the least role in increasing coronavirus cases and active cases, this gas has had a significant effect on the number of deaths and has been very dangerous in this regard .Hydrofluorocarbons (HFC): HFC gas has been ranked fifth, fourth, and fifth in influencing coronavirus, active, and death cases.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This might be due to the upregulation of PAX6 by glucagon-like peptide 1 receptor agonists ( 30 ), which promoted the regeneration of insulin-secreting cells. In addition, MODY5 patients might benefit from Bacillus Calmette – Guerin (BCG) vaccination ( 31 ). Studies showed that BCG treatment might regenerate pancreatic B cell ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%